THE IMPLEMENTATION OF TRADE RELATED INVESTMENT MEASURES IN LAW OF REPUBLIC OF INDONESIA NUMBER 25 OF 2007 CONCERNING INVESTMENT - Selviana Purba (Lex Lectio Law Journal, 2025)
This paper examines the implementation of the Agreement on Trade-Related Investment Measures (TRIMS) within the legal framework of the Republic of Indonesia, particularly through Law Number 25 of 2007 concerning Investment. As a member of the World Trade Organization (WTO) since 1995, Indonesia is required to harmonize its investment policies with international trade principles, especially the National Treatment and the Prohibition of Quantitative Restrictions as reflected in GATT 1994. Although Indonesia received special and differential treatment that allowed a longer transition period, the alignment of domestic investment laws with TRIMS obligations remains essential to ensure fair competition and prevent trade-distorting investment measures. This paper analyzes how Indonesia incorporates TRIMS principles into its national investment regulations, with particular attention to Article 18 of the Investment Law, which provides various investment facilities but potentially raises issues related to performance requirements. The study concludes that while Indonesia has made significant progress in integrating TRIMS-compatible rules, several provisions—especially those linking incentives to the use of domestic goods—may still pose risks of inconsistency with WTO commitments.